IMPACTO AMBIENTAL POR USO DEL GAS NATURAL DE CAMISEA EN LA GENERACIÓN DE ENERGÍA ELÉCTRICA EN EL PERÚ - Sarango J., Douglas D. (2005)
In this study was determined the environment impact for Camisea natural gas used in the electrical energy generating for the National Electric System (SEIN), during 2004-2020 period. The amount of C, CH4, N20, NOx, COy NMCOV, were not emited to the environment for Camisea natural gas use, this energy source replaced Diesel 2, Residual S, Residual 500, Residual 6 y Coal. These emissions are depended offuel type, thermoelectric power plant annual energy generation and other factors of emissions dueto buming fuels in the Peru's Electric Sector. The Wien Automatic System Planning For Power Generating System Expansion Plannning - WASP III model was used to get the expansion optimization of the generation for mínimum cost for SEIN in the long tenn 2004-2020 period. This model was developed for Intemational Atomic Energy Agency (IAEA) and World Bank, at the end of 80'.